'A critique of culture': Alan Watts, psychedelic Buddhism, and religious play in postwar America. (2nd October 2017) - Shipley, Morgan
ABSTRACT: Heralded as a time of economic prosperity, the post-World War II period in America also experienced extraordinary religious awakenings of born-again evangelicalism, Prosperity Gospels, and an apocalyptic flare rendered palpable by atomic bombs and the Cold War. Postwar Christianity found itself reinforcing neoliberalism, sanctifying standardizations accompanying technological routinization, economic progress, and consumption-based lifestyles, resulting in alienating crises of spirit and culture. Amidst uncertainty and conformity, psychedelics offered sacramental means for bypassing postwar society's mechanisms by uncovering expressions of mutuality and compassion. Outlined within Alan Watts' work, psychedelics unveiled Buddhist wisdom, detailing existence not as a function of difference, but as an expression of absolute interconnection. Neither doctrinaire nor authoritarian, Watts' psychedelic engagement with Buddhism invites us to investigate beyond differences, toward moments in which the subjective self becomes an unselfish expression of the absolute 'other'.